Pathway profiling of a novel SRC inhibitor, AZD0424, in combination with MEK inhibitors for cancer treatment. Issue 5 (18th December 2021) - Dawson, John C.; Munro, Alison; Macleod, Kenneth; Muir, Morwenna; Timpson, Paul; Williams, Robert J.; Frame, Margaret; Brunton, Valerie G.; Carragher, Neil O.
Abstract : A more comprehensive understanding of how cells respond to drug intervention, the likely immediate signalling responses and how resistance may develop within different microenvironments will help inform treatment regimes. The nonreceptor tyrosine kinase SRC regulates many cellular signalling processes, and pharmacological inhibition has long been a target of cancer drug discovery projects. Here, we describe the in vitro and in vivo characterisation of the small‐molecule SRC inhibitor AZD0424. We show that AZD0424 potently inhibits the phosphorylation of tyrosine‐419 of SRC (IC50 ~ 100 nm ) in many cancer cell lines; however, inhibition of cell viability, via a G1 cell cycle arrest, was observed only in a subset of cancer cell lines in the low (on target) micromolar range. We profiled the changes in intracellular pathway signalling in cancer cells following exposure to AZD0424 and other targeted therapies using reverse‐phase protein array (RPPA) analysis. We demonstrate that SRC is activated in response to treatment of KRAS‐mutant colorectal cell lines with MEK inhibitors (trametinib or AZD6244) and that AZD0424 abrogates this. Cell lines treated with trametinib or AZD6244 in combination with AZD0424 had reduced EGFR, FAK and SRC compensatory activation, and cell viability was synergistically inhibited. In vivo, trametinib treatment of mice‐bearing HCT116 tumours increased phosphorylation of SRC on Tyr419, and, when combined with AZD0424, inhibition of tumour growth was greater than with trametinib alone. We also demonstrate that drug‐induced resistance to trametinib is not re‐sensitised by AZD0424 treatment in vitro, likely as a result of multiple compensatory signalling mechanisms; however, inhibition of SRC remains an effective way to block invasion of trametinib‐resistant tumour cells. These data imply that SRC inhibition may offer a useful addition to MEK inhibitor combination strategies. Abstract : We identified compensatory activation of SRC family kinases using reverse‐phase protein array (RPPA) analysis to profile the protein and phosphoprotein expression of KRAS mutant colorectal cancer cell lines treated with MEK inhibitors. We demonstrated that this compensatory signalling could be inhibited using SRC inhibitors and that combination of SRC with MEK inhibitors may offer a useful combination strategy.